Studi Dekonstruksi: Menyingkap Identitas Muslimah Di Media Rahma.id - Mawlana, Akbar; Ulumuddin, Naufalul Ihya; Pratama, Adhitya Prasta (Jurnal Common, 2022)
Women in Islam are subjects who often experience recognition instability. Instability is formed through universality logocentrism that has been established in people's consciousness. People's judgments always focus "at the center", but forget about something that goes "on the periphery". This study aims to deconstruct the identity of Muslim women who have been constructed as weak, powerless, and imprisoned subjects by religious and cultural representations. Media studies are the main focus of this research. The choice of media studies departs from the postmodern reality that cannot be separated from text and media. Rahma.id is the main focus of this media. The election of Rahma.id because it is oriented towards Muslim women, as well as being a new media that has accommodated many narratives about women, gender, and Islam. Derrida's deconstruction becomes a knife of analysis, considering his concept that wants to break the establishment of modern society by reading differance. Through Derrida's deconstruction, we get the result that there are gender values ​​that are forgotten to become narratives in the media. In fact, Muslim women have multicultural, multi-perspective, and multi-disciplinary characters.